Development of a Measure of Informal Workplace Social Interactions - Winslow, Carolyn J.; Sabat, Isaac E.; Anderson, Amanda J.; Kaplan, Seth A.; Miller, Sarah J. (Frontiers in Psychology, 2019)
A measure of informal, non-task-related workplace social interactions that captures both the frequency of interactions and the positive affect that can accompany such interactions was developed and validated. In two samples of employees (N =188 and N = 315, respectively), the factor structure, reliability, and incremental predictive validity of the newly-developed measure were evaluated. Results support the anticipated two-factor structure, demonstrate strong psychometric properties, and reveal that the new measure explains additional variance in employee outcomes (job satisfaction and job-related positive affect). This newly-developed, 16-item scale provides a psychometrically sound measure for researchers and organizations to use in assessing, and potentially improving, two dimensions of workplace social interactions.